Polymerization process modeling - Dotson, Neil A.; Galvan, Rafael.; Laurence, Robert L.; Tirrell, Matthew. (VCH, 1996)
This book is about: Distinctive features of polymers and polymerization reactors; Step growth polymerization; Copolymerization; Nonlinear polymerization;...